Guidelines to prepare for practical classes on therapeutic dentistry. - Dmitrieva, E. A. (Морфологія / Morphologia / Morfologìâ, 2015)
The article highlights the main approaches to preparation of practical training on therapeutic stomatology and presents methodological recommendations on collecting and systematization of education materials. The article is focused on the role of practical training in educational process as one of the main forms of obtaining and consolidating theoretical knowledge and practical skills for students.